Graphene-based frustrated Lewis pairs as bifunctional catalysts for CO2 reduction via the dissociative chemisorption of molecular H-2: a periodic density functional perspective - Senthamaraikannan, Thillai Govindaraja; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj (New Journal of Chemistry, 2021)
Nanocarbon-based frustrated Lewis pair (FLP) bifunctional catalysts, on account of their unquenched electron transfer property, are becoming increasingly attractive as catalysts for the CO2 reduction reaction via the dissociative chemisorption of H-2. In the present study, we propose a nanocarbon-based FLP catalyst. The pair comprises nitrogen doped/phosphorus doped graphene as Lewis bases and M(C6F5)(3) (M = B, Al, Ga, and In) as Lewis acids. The computational investigation reveals that the carbon atoms adjacent to the doped N and P atoms are the active sites towards the dissociative chemisorption of hydrogen molecule. The analyses of the Bader charges and difference charge densities validate the dissociative chemisorption of H-2 molecule and the fact that a significant electron redistribution promotes the polarization of the hydrogen molecule. Density of states confirms the hybridization between the p-states of the nitrogen/phosphorus atom and the s-state of hydrogen atom in all FLPs. The dissociative chemisorption of hydrogen is noted in all FLP complexes, thereby facilitating a low barrier reaction path for CO2 reduction. Between P-doped and N-doped FLPs, N-doped FLP catalysts prove to be a more promising counterpart with considerably low activation barriers, ranging between 0.01 and 0.11 eV, towards CO2 reduction. Thus, the present study demonstrates the great potential of doped carbon-based FLPs as novel nanostructure catalysts for CO2 reduction via the direct utilization of molecular hydrogen.

Graphitic carbon nitride supported boron quantum dots: a transition metal free alternative for di-nitrogen to ammonia reaction - Samudre, Nikhil S.; Krishnamurty, Sailaja (CHEMPHYSCHEM, 2025)
Presently, a sustainable electrochemical Nitrogen Reduction Reaction (NRR) has been essentially found to be viable on transition metal-based catalysts. However, being cost-effective and non-corrosive, metal-free catalysts present an ideal solution for a sustainable world. Herein, through a DFT-based study, we demonstrate metal-free NRR catalysts, boron quantum dots with 13 atoms as a case study and their chemically modified counterparts when anchored on graphitic carbon nitride (g-C3N4) surface. The best catalyst among the studied, a silicon-doped boron quantum dot with a cagelike structure, is found to favour the dinitrogen to ammonia reaction pathway with a low liming potential and potential rate-determining step (PDS) of -0.11 V and 0.27 eV, respectively. The present work demonstrates as to how boron quantum dots, which are reported to be experimentally synthesised, can be exploited for ammonia synthesis when supported on the surface. These catalysts effectively suppress the HER, thus establishing its suitability as an ideal catalyst. The work also represents a futuristic pathway towards a metal-free catalyst for NRR.
Keywords: Boron quantum dot; Electro-catalyst; Graphitic carbon nitride; hydrogen evolution reaction; Limiting potential; metal free catalyst; Nitrogen Reduction Reaction